US-CHINA DIGITAL INFRASTRUCTURE COMPETITION IN SOUTHEAST ASIA: STRATEGIES AND IMPLICATIONS FOR ASEAN'S 5G FUTURE (Journal of International Studies, 2025)
The rapid evolution of the digital economy has significantly heightened global competition between the United States and China, especially in the area of digital infrastructure development centred around 5G technology. This competition situates the ASEAN member states (AMS) at a strategic intersection of these two superpowers, compelling them to manoeuver through a complex geopolitical landscape. This study seeks to analyse the strategies that the United States and China are deploying in Southeast Asia’s digital infrastructure, with a particular focus on 5G technology, and to evaluate the implications for the digital future of ASEAN.The study utilises a comprehensive literature review methodology, scrutinising relevant scholarly articles, policy documents, and reports from the period 2013 to 2023. Despite the United States' escalating security concerns regarding Chinese technology, the AMS has opted for a balanced and diversified approach in selecting their 5G vendors. This strategy demonstrates their attempt to harmonise technological advancement with security imperatives.The findings indicate that AMS has preserved their strategic autonomy in the face of U.S.-China competition by diversifying their technological partnerships and avoiding dependence on any single supplier. Nonetheless, this approach presents substantial challenges, including economic vulnerabilities, security risks, and the intricacies of geopolitical entanglements. The article anticipates that AMS will continue to adeptly balance their relationships with both the United States and China, targeting digital sovereignty that aligns with their long-term developmental goals. This study contributes fresh insights into the digital geopolitical dynamics of Southeast Asia and provides valuable perspectives for policymakers and business entities operating within this complex environment.